Correlation of cardiovascular risk predictors with overweight and obesity in patients with familial hypercholesterolemia - Wang, Yaodong; He, Jinchun (Frontiers in Cardiovascular Medicine, 2022)
Purpose We aimed to analyze the correlation between overweight and obesity-related indicators and cardiovascular risk predictors in patients with familial hypercholesterolemia (FH) and to evaluate their mutual predictive properties. Methods A total of 103 patients with FH included from 2004 to 2017 were retrospectively analyzed. Pearson correlation analysis and multiple linear regression analysis were used to assess the correlation between overweight and obesity-related indicators and cardiovascular risk predictors in FH patients. Subject operating characteristic (ROC) curve was used to analyze their reciprocal predictive performance. Results (1) Atherogenic index of plasma (AIP) (β = 0.020) and ApoB/ApoA1 Ratio (BAR) (β = 0.015) were independently correlated with body mass index (BMI) (P < 0.05); AIP (β = 1.176) was independently correlated with waist-to-hip ratio (WHR) (P < 0.01); AIP (β = 1.575), BAR (β = 0.661) and atherogenic coefficient (AC) (β = 0.427) were independently correlated with waist-to-height ratio (WHtR) (P < 0.05). (2) The area under the ROC (AUC) for overweight corresponding to AIP, BAR, and AC were 0.695 (95% CI = 0.593–0.797, P < 0.01), 0.660 (95% CI = 0.555–0.766, P < 0.01), and 0.632 (95% CI = 0.525–0.740, P < 0.05), respectively; and AUCs for central obesity corresponding to AIP, BAR and AC were 0.757 (95% CI = 0.656–0.857, P < 0.001), 0.654 (95% CI = 0.536–0.771, P < 0.05) and 0.651 (95% CI = 0.538–0.764, P < 0.05), respectively. The AUCs for moderate risk of AIP corresponding to BMI, WHR, and WHtR were 0.709 (95% CI = 0.608–0.811, P < 0.001), 0.773 (95% CI = 0.678–0.867, P < 0.001), 0.739 (95% CI = 0.641–0.836, P < 0.001), respectively, and BMI, WHR and WHtR corresponded to an AUC of 0.691 (95% CI = 0.585–0.797, P < 0.01), 0.734 (95% CI = 0.632–0.835, P < 0.001), and 0.706 (95% CI = 0.603–0.810, P < 0.01) for high risk of AIP, respectively. Conclusion AIP has independent positive linear correlation with indicators related to overweight and obesity in FH patients; AIP has good predictive performance for overweight and obesity in FH patients, and WHR has good performance for identifying moderate and high risk of AIP in FH patients.